FDI spillovers at regional level : evidence from Portugal - Crespo, Nuno (2010)
This paper aims to establish whether geographical proximity between the locations of multinational firms and domestic firms facilitates the occurrence of FDI spillovers. Using data for Portugal, this hypothesis is clearly confirmed. However, the impact varies according to whether the externalities considered are horizontal or vertical. In the first case, the impact is negative, which may result from the competition effect at regional level. With regard to vertical externalities, a positive impact through backward linkages is observed. These results raise important implications for the definition of economic policies aiming to attract FDI and promote regional development.